ANALYSIS OF THE THEORY AND PRACTICE OF THE FORMATION OF THE ARCHITECTURAL ENVIRONMENT OF LIBRARIES - Chevposa, Veronica; Kryzhanivskyi, Oleksandr; Gnatiuk, Liliia (Theory and practice of design, 2024)
The study of the article is aimed at the development and theoretical and practical substantiation of the principles of public library organization. Analyzing the source base and scientific works devoted to the design of libraries in Ukraine, a study of the current state of the considered problem was conducted and the need to develop the features of the functional and planning organization of libraries, which is the most urgent problem in modern Ukraine, was determined for the purpose of architectural and planning activities in the urban environment. Within the framework of the study, the features of the architectural and planning organization of libraries were developed and theoretically substantiated, including organizational and methodological aspects (such as stock selection, compliance with user needs, technological support), functional and planning characteristics (functionality of space, universality of space, differentiation of space availability) and capacitive-spatial features (localization, individualization of the image, functional dominant). Purpose. The purpose of the study is to design the space taking into account convenience and functionality. This may include areas for reading, workplaces, creative laboratories, children’s corners and other functional elements. Ensuring easy access to the library and educational space for all residents of the city. This can mean open access, flexible working hours and accessibility for different social groups, including children, young people, the elderly and vulnerable population groups. Methodology. Research methods: analysis of literary sources, materials related to the functional and planning organization of public libraries in Ukraine. Analysis of foreign and domestic experience in designing libraries, observation of object development, systematization and classification of libraries, comparative analysis. Results: familiarization with the current state of the studied problem. Disclosure of the essence and terminological apparatus. A historical analysis of the evolution of public libraries was carried out. Theoretically justified key features of the functional and planning structure of the object. Scientific novelty. The principles of the organization of space and the formation of public libraries are defined and characterized, as well as the prospects for their development in Ukraine are highlighted. Practical significance. This article can be used as a resource in developing library projects and conducting scientific research on this topic.